2018
DOI: 10.3348/kjr.2018.19.4.803
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Report of Pilot Study for the Korean Lung Cancer Screening (K-LUCAS) Project: Feasibility of Implementing Lung Imaging Reporting and Data System

Abstract: ObjectiveTo report the radiological results of a pilot study for the Korean Lung Cancer Screening project conducted to evaluate the feasibility of lung cancer screening using low-dose chest computed tomography (LDCT) in Korea.Materials and MethodsThe National Cancer Center and three regional cancer centers participated in this study. Asymptomatic current or ex-smokers aged 55–74 years with a smoking history of at least 30 pack-years who had used tobacco within the last 15 years were considered eligible. In tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 12 publications
0
28
0
Order By: Relevance
“…Lung-RADS category 2 (benign appearance) represents as negative screening results, while categories 3 (probably benign) and 4 (suspicious) represent positive results. 15 Since most of MIA or AIS, even part of invasive adenocarcinoma may appear as pGGNs companied with a well-circumscribed interface, 16 the majority of pGGNs were categorised as 2 or 3 according to the Lung-RADS version 1.1, which might increase the rate of underdiagnosis. Biological tumor studies have revealed that vasculature remodeling or neoangiogenesis is one of the first occurring events in the early stage of tumor development.…”
Section: Lung-rads Version 11 and Its Complementary Lung-rads Systemmentioning
confidence: 99%
“…Lung-RADS category 2 (benign appearance) represents as negative screening results, while categories 3 (probably benign) and 4 (suspicious) represent positive results. 15 Since most of MIA or AIS, even part of invasive adenocarcinoma may appear as pGGNs companied with a well-circumscribed interface, 16 the majority of pGGNs were categorised as 2 or 3 according to the Lung-RADS version 1.1, which might increase the rate of underdiagnosis. Biological tumor studies have revealed that vasculature remodeling or neoangiogenesis is one of the first occurring events in the early stage of tumor development.…”
Section: Lung-rads Version 11 and Its Complementary Lung-rads Systemmentioning
confidence: 99%
“…In 2017, a K-LUCAS Project, a 2-year multicenter lung cancer screening pilot project, was initiated to as evaluate the effectiveness and feasibility of lung cancer screening and validate new standards for the reporting form of LDCT and the quality of the screening by a web-based network system, and develop a risk prediction model for lung cancer 74,76. This project was sponsored by National Cancer Center and collaborated with Multidisciplinary Expert Committee.…”
Section: Ldct Screening For Lung Cancer In Asiamentioning
confidence: 99%
“…Specifically, in the National Lung Screening Trial, in current or ex-smokers aged 55–74 years who had a smoking history of at least 30 pack-years and had quit within the last 15 years, lung cancer specific mortality was 20.0% lower in the LDCT screening arm than in the chest X-ray screening arm ( 1 ). On the basis of this result, the Korean Lung Cancer Screening (K-LUCAS) project had been launched and the pilot study for K-LUCAS was performed to evaluate the feasibility on the implementation of national screening with LDCT for high-risk subject of lung cancer ( 2 ).…”
Section: Introductionmentioning
confidence: 99%